Review Related Reviews: Multiband Planar Inverted Antenna for Mobile Communication - Ma’rifah, Puteri Nurul; Rohadi, Erfan; Siradjuddin, Indrazno; Junus, Mochammad (International Journal of Frontier Technology and Engineering, 2022)
Research in the field of planar inverted antennas with multiband frequencies is currently being developed. Due to the hugely increased number of mobile users, at least every time a new generation is released, a mobile communication system is released with additional features. All additional features of a mobile communication system require an antenna that resonates over a specific frequency spectrum range, meaning multiple antennas are required in a single mobile device to function across all generations for all frequency spectrums. To reduce the number of antennas on a mobile communication system device, it is necessary to design a new type of antenna that operates in a different frequency range. The inverted planar multiband antenna is designed to have changing sizes, shapes, and material properties. Types of inverted planar antennas include planar inverted-L antennas (PILA) and planar inverted-F antennas (PIFA). After analysis, the antenna designed by Juan Zhang et al. is the best solution for mobile communication systems. The designed antenna has compact antenna dimensions and four frequency bands that can be applied to N1/N78/N79 5G and 5.8 GHz WLAN. The antenna has a high gain of almost 5dB in the 5.60–7.00 GHz frequency range. They also claim that the antenna has a beam efficiency of four very high-frequency antenna points and a small side lobe that appears only at the top at the highest frequency point. But unfortunately, the antenna cannot cover the entire frequency range that must exist in a mobile communication system